2014
DOI: 10.1038/tpj.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Impact of GATA4 variants on stable warfarin doses in patients with prosthetic heart valves

Abstract: Interindividual variability in stable warfarin doses is largely attributed to VKORC1 and CYP2C9 variants. On the basis of a recent finding of the role of GATA4 in control of CYP2C9 expression, we tested a possible effect of GATA4 genotypes on variability in warfarin response using 201 Korean patients with prosthetic cardiac valves. Two single-nucleotide polymorphisms (SNPs), rs2645400 (G>T) and rs4841588 (G>T), were significantly associated with stable warfarin doses in patients carrying CYP2C9 wild-type homoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…However, the results of the present study did not corroborate an association between other NRs GATA4, ESR1, NR1I2, and HNF4α polymorphisms and warfarin dose, suggested by Moon et al [12,13] and Jeong et al [14]. Indeed, in three separate research studies performed on a single population of 201 Korean patients with prosthetic cardiac valve, they found that GATA4 variants rs2645400 and rs4841588, rs2472682 in the NR1I2, and the combination of rs2501873 in the ESR1 and rs3212198 in the HNF4A, were marginally associated with warfarin dose requirements.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, the results of the present study did not corroborate an association between other NRs GATA4, ESR1, NR1I2, and HNF4α polymorphisms and warfarin dose, suggested by Moon et al [12,13] and Jeong et al [14]. Indeed, in three separate research studies performed on a single population of 201 Korean patients with prosthetic cardiac valve, they found that GATA4 variants rs2645400 and rs4841588, rs2472682 in the NR1I2, and the combination of rs2501873 in the ESR1 and rs3212198 in the HNF4A, were marginally associated with warfarin dose requirements.…”
Section: Discussioncontrasting
confidence: 55%
“…We have also considered the association of the three VDR variants with stable warfarin dose requirements at 3 months by excluding CYP2C9 and VKORC1 activity status from the list of adjustment variables. Results show that associations are strongly maintained with rs11168292 (Beta (SE) = 0.083 (0.022); P = 1.26 × 10 We have also tested for the allelic association of four out of five additional SNPs that have been previously reported in the literature [12][13][14] for association with warfarin dose (Table 3). No significant association was detected between warfarin dose requirements and rs2501873 in the ESR1 (P = 0.486), rs2472682 in the NR1I2 (0.868), rs2645400 (P = 0.144), and rs4841588 (P = 0.402) in GATA4.…”
Section: Association Of Nr Gene Polymorphisms and Warfarin Dosementioning
confidence: 99%
See 1 more Smart Citation
“…[25] Warfarin is an anti-coagulant and is used as a preventive for the formation of blood clots in blood vessels and their migration. [26] For the gene ESR1, the SNP variant associations of rs9340799 and rs4870061, and rs1801132 and rs2234693 were found to influence the drug therapy of prescribed drugs Letrozole, Raloxifene, Tamoxifen, Atorvastatin, and Anastrozole.…”
Section: Pharmacogenetic Implication Studymentioning
confidence: 99%
“…Several studies revealed that GGCX gene polymorphisms in Asian populations could be a factor on warfarin dose requirements [7,8]. Recently, our study group showed that polymorphism of GATA4, a transcription factor of CYP2C9, was marginally associated with warfarin responses [9]. Nevertheless, a large part of variability in the warfarin dose requirements remains unexplained.…”
Section: Introductionmentioning
confidence: 97%